(untitled) (Eurasian Journal of Religious Studies, 2021)
Religious beliefs can be combined with nationalism to provide a source mobilization for national self-determination. With the declining of quasi-state "Islamic State", there is a temporary power vacuum in the former ISIS’ controlled territory. Similar like in the post-colonial and post-cold war eras, when the withdrawal of external powers created a power vacuum, religious nationalism involved in the reconstruction of subsequent orders, and the new regime often embodied criticism and revision of the previous political system, political structure, and ruling culture. The cultural environment of Islam shapes indigenous nationalism. Religious beliefs can provide sources of aggregation and mobilization for self-determination. This paper argues that since the ISIS showed extremism characteristics of the close combination of violence and religion, those national independent forces, rooted in the local religious society, have to revalue their religious security. Key words: religious nationalism, power vacuum, Islamism, Kurds, Middle East, self-determination